Pemetaan Daerah Semburan Lumpur Sebagai Kajian Awal Dampak Bencana Menggunakan Metode Self-Potential Di Desa Napan-NTT. - Yanti Boimau; Hilary F. Lipikuni; Anastasia K. D. Lestary (Universitas Andalas, 2026)
Research has been conducted in the mudflow area of Napan village, Kefamenanu-NTT. The aim of this study is to identify fluid flow or mudflow in the research area using the Self-potential method. Data acquisition In this study, a closed loop system was used. Based on the distribution of potential values on the isopotential map, the research location shows low anomalies which indicate that the area is conductive. The low potential anomaly value in the research area is caused by the presence of subsurface mudflow along the measurement path. The direction of the mudflow fluid flow in Napan village is predicted to be in the measurement area of the research location. Based on the results of the interpretation of the measurement area, it has the potential to become a weak zone which has the potential to become a location for the emergence of new mudflow sources if there is a change in hydrogeological conditions.